Potret Politisi Perempuan Kabupaten Dharmasraya (Studi tentang Potret Anggota Legislatif Perempuan Kabupaten Dharmasraya periode Tahun 2019-2024) - Weli Andola; Novi Budiman (Politik Islam, 2024)
It is illustrated that women in Indonesia, including in Dharmasraya Regency, still face various obstacles in entering and surviving in politics. Patriarchal culture, internal constraints such as domestic roles, and external constraints such as a political system that still favors men are the main factors that hinder women's participation in politics. So this research aims to find out how the portrait background of female legislative members of Dharmasraya Regency in the 2019-2024 period, the strategy of female legislative members in winning Pileg in Dharmasraya Regency, and the role of female legislative members of Dharmasraya Regency in the formation of local policiesThis research method uses a qualitative method. The data collection techniques that researchers use are observation, interviews and documentation. The data obtained were analyzed using three stages, namely data reduction, data presentation, and drawing conclusionsWomen Legislative Members of Dharmasraya Regency still do not meet the 30% quota. The lack of women's representation in the 2019 legislative elections held in Dharmasraya Regency only had 2 female candidates who managed to occupy parliamentary seats: Elisa Septiani and Sasmi Erli. The strategies used by the legislature in winning the legislative general election include: formulation of vision and mission, assessment of the situation and evaluation of the role of the Dhamasraya Regency Women's DPRD as a form of community representation in controlling gender responsive policies related to development in Dharmasraya Regency. Because women's thoughts and feelings will be able to collaborate to prioritize ongoing gender-responsive policies. Therefore, the role of women politicians is very important in the process of making until the birth of the 2019-2024 Dharmasraya Regency regional regulations.